Heat and Velocity Parameters of a Non-Isothermal Flow Generated by a Double-Chamber Air Diffuser - Klymenko Hanna (Selected Scientific Papers: Journal of Civil Engineering, 2012)
Heat and velocity parameters of the non-isothermal flow generated by a source panel-type double-chamber air diffuser with four horizontal shelf pressure equalizers of optimal relative length at the mid-horizontal level and in the vertical axisymmetrical plane. Irregularity ratios of initial velocities and temperatures of the air flow under study have also been defined.